Improving the Welfare of MSMEs Through Strengthening Financial Management: A Practical and Innovative Approach - Sulistiana, Indra; Febriana, Febby; Rahmat, Ariawan; Hendrawan, Putri Nur Aeni; Andriyani, Yeni (Abdimas Indonesian Journal, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a vital role in the economy, especially in creating jobs and supporting local economic growth. However, one of the main challenges faced by MSMEs is the lack of understanding and skills in financial management. Many MSMEs face problems in managing their finances that can hinder the growth and sustainability of their businesses. This community service activity aims to improve the welfare of MSMEs through strengthening financial management with a practical and innovative approach. We organize training workshops on the use of financial technology, individual consultation sessions, and business plan development. Through this approach, we provide MSMEs with practical knowledge and skills so that they can manage their finances more effectively and sustainably. The output targets of the activity are increasing MSME knowledge and understanding of financial management, improving practical skills in financial management among MSMEs, adopting innovative approaches in MSME financial management, and improving the welfare and sustainability of MSME businesses.